Pengaruh Efikasi Diri Dan Motivasi Kerja Terhadap Kinerja Guru Penggerak Angkatan 4 Kabupaten Mandailing Natal - Sulhan Hamid H Lubis; Saut Purba; Paningkat Siburian; Osberth Sinaga (Syntax Idea, 2022)
The purpose of this study is to describe: 1) the effect of self-efficacy on the performance of the driving teacher, 2) the effect of work motivation on the performance of the driving teacher, and 3) the effect of self-efficacy and work motivation on the performance of the driving teacher. This research design is in the form of an explanation. The subjects of this study were all teachers in Mandailing Natal Regency, totaling 60 people. The instrument of data collection was through a questionnaire. Data analysis used inferential statistical analysis with multiple linear regression analysis. Based on the results of data analysis, the coefficient of Freg = 0.809; sig. 0.450. the higher the self-efficacy and the higher the work motivation, the higher the performance. On the other hand, the lower the self-efficacy and the lower the work motivation, the lower the performance of the driving teacher. Based on the results of this study, it can be stated that the hypothesis proposed in this study is accepted. The results of this study also prove that self-efficacy and work motivation contribute 36.186% to performance. This means that the two variables (self-efficacy and work motivation) contribute 36.186% to the high and low performance.